2013
DOI: 10.1002/pat.3150
|View full text |Cite
|
Sign up to set email alerts
|

States of water, surface and rheological characterisation of a new biohydrogel as articular cartilage substitute

Abstract: PVA based hydrogel was synthesised using, as crosslinking agent, trisodium trimetaphosphate (STMP) and its morphology was modified inducing a microporous structure to obtain potential substitutes for cartilage tissue. The hydrogel was characterised by Infrared Spectroscopy combined with Time of flight mass spectrometry (ToF-SIMS) that confirmed the successful occurrence of crosslinking reaction, the hyphotised crosslinking arm and its homogeneous distribution. The mechanical spectra of the fully hydrated sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…The storage modulus (G′), loss modulus (G″) and phase angle of PU hydrogels are analyzed as a function of frequency at 37°C. As shown in Figure a, G′ and G″ of all hydrogels are on the same order of magnitude respectively, and G′ is always one order of magnitude higher than G″ of each sample, indicating that all the hydrogels show strong “gel‐like” elastic behavior (Leone, Bidini, Lamponi, & Magnani, ). G′ remains in a certain constant range with the increase of frequency, which indicates stability and structural integrity of each crosslinked hydrogel.…”
Section: Resultsmentioning
confidence: 90%
“…The storage modulus (G′), loss modulus (G″) and phase angle of PU hydrogels are analyzed as a function of frequency at 37°C. As shown in Figure a, G′ and G″ of all hydrogels are on the same order of magnitude respectively, and G′ is always one order of magnitude higher than G″ of each sample, indicating that all the hydrogels show strong “gel‐like” elastic behavior (Leone, Bidini, Lamponi, & Magnani, ). G′ remains in a certain constant range with the increase of frequency, which indicates stability and structural integrity of each crosslinked hydrogel.…”
Section: Resultsmentioning
confidence: 90%
“…They can mimic the native extracellular matrix with compositional and mechanical similarity to cartilage. 25 , 26 The rheological behavior of cell-free hydrogels, as examined by a dynamic mechanical analyzer, revealed that the moderate range of E′ of Alg/Col gel (90 kPa) being similar to that of tibia cartilage (30 ~ 110 kPa) 27 may be favorable for cells to sense and secrete cartilaginous matrix.…”
Section: Discussionmentioning
confidence: 99%
“…The reaction mixture was stirred for 2 h. The obtained hydrogel was then layered into a petri dish and the obtained soft film (first layer) was rinsed with large volumes of distilled water until no weight loss could be detected. 11,12 The best nHA/PVA molar ratio was identified through rheological analysis. The sample with the lowest ratio (nHA/PVA 0.010) showed poor rheological properties for the foreseen application.…”
Section: Samples Preparationmentioning
confidence: 99%
“…Water content. As previously described, 12 the three regimes into which water can be distinguished, namely non-freezing water, bound-freezing water and freezing water (or bulk water) were quantified by DSC. 15 The weight of completely swollen hydrogels (WSG) and the total weight of water inside the network (WH) were detected by TGA.…”
Section: Sample Characterizationmentioning
confidence: 99%
See 1 more Smart Citation